Negotiating war on TV series: A cross-national comparative study of the 2003 invasion of Iraq. Issue 1 (1st April 2016) - Al-Rawi, Ahmed
The article investigates three TV series that examined the way the 2003 war on Iraq was represented. The TV series analysed are the American Generation Kill (2008), the British Occupation (2009) and the Arabic Hudu' Nisbi/Relatively Calm (2009) produced during the Muslim month of Ramadan. The research investigates the way the war on Iraq is shown by the three different TV series by linking their cultural and political contexts. Though the three TV series agree on several issues such as the destructive impact of the US-led occupation, they differ in their focus on presenting the deadly impact of war on civilians and the psychological trauma soldiers go through. Partly based on the subaltern concept, the study argues that the three TV dramas are cultural expressions by which power inequality is negotiated between the subaltern natives and hegemonic powers.